Analysis Of Consumer Behavior Towards Purchasing Decisions And Consumer Satisfaction Of"Harum Enaks" Powdered Pepper In Pangkalpinang City - Artiani; Eni Karsiningsih; Maya Mustika; Hana Lamisa (International Journal of Economics, Business and Innovation Research, 2026)
The Bangka Belitung Islands Province is a center of white pepper production in Indonesia, known for its Muntok White Pepper brand. Muntok White Pepper is generally sold in unprocessed granules, thus limiting its added value. Efforts to increase added value include converting granules into ground pepper. One such ground pepper produced in Bangka Belitung is the "Harum Enak" brand. This "Harum Enak" ground pepper is produced by PT Pelangi Nusantara Sehati, located in Sungailiat, Bangka. This study aims to 1) analyze the effect of price on purchasing decisions for "Harum Enak" ground pepper in Pangkalpinang City, 2) analyze the effect of product quality on purchasing decisions for "Harum Enak" ground pepper in Pangkalpinang City, 3) analyze the effect of price on consumer satisfaction for "Harum Enak" ground pepper in Pangkalpinang City, 4) analyze the effect of product quality on consumer satisfaction for "Harum Enak" ground pepper in Pangkalpinang City, 5) analyze the effect of purchasing decisions on consumer satisfaction for "Harum Enak" ground pepper in Pangkalpinang City, 6) analyze the effect of price on consumer satisfaction through decisions for "Harum Enak" ground pepper in Pangkalpinang City, and 7) analyze the effect of product quality on consumer satisfaction through decisions for "Harum Enak" ground pepper in Pangkalpinang City. The study used a survey method with accidental sampling to collect data from 100 respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The study's direct-effect results show that price has a positive and significant effect on purchasing decisions for "Harum Enak" ground pepper in Pangkalpinang City. Still, it does not have a positive and significant effect on consumer satisfaction. Product quality has a positive and significant effect on purchasing decisions, but does not affect consumer satisfaction; purchasing decisions, in turn, have a positive effect on consumer satisfaction. In the indirect effect, price does not have a positive and significant effect on consumer satisfaction through purchasing decisions, whereas product quality does.